Embedding Space in African Society
VIII, 279 p.
Keywords: This book provides a detailed insight into how space and its applications are embedded, and can be further embedded, into African society in support of the SDGs, while taking into account the specific features, needs, and diversity of that society. Contributions drawn from across the continent and further afield provide analyses of the particular social situations in a variety of different African countries and regions, and highlight areas where space applications support the SDGs, and where they can further do so. The chapters cover a wide array of relevant and timely topics including basic needs like water quality, education, and capacity building, as well as financial, security, and legal aspects, together with facets of space technologies and infrastructure in Africa. Embedding Space in African Society will be of great interest to students and professionals in sustainable development, governance, and space studies.